2023
DOI: 10.3390/plants12051142
|View full text |Cite
|
Sign up to set email alerts
|

From the Wild to the Field: Documentation, Propagation, Pilot Cultivation, Fertilization, and Phytochemical Evaluation of the Neglected and Underutilized Amelanchier ovalis Medik. (Rosaceae)

Abstract: The snowy Mespilus, or serviceberry (Amelanchier ovalis Medik., Rosaceae) represents a neglected and underutilized small fruit tree species with high nutritional value. In this work, we present the results of a long-term study facilitating the sustainable exploitation of A. ovalis as a new germplasm resource from the Greek flora. Ten wild-growing population samples of A. ovalis have been collected from natural habitats in northern Greece. Asexual propagation trials on these materials delivered successful propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…From the current data, the fact that larger fruits had a similar cumulative weight to smaller fruit, may indicate variations in crop load in terms of the response of distinct genotypes to fertilization treatments; however, from the current results, no clear conclusion can be drawn. In wild germplasm of other tree crops like Amelanchier ovalis that has been experimentally cultivated, the application of conventional fertilization increased the fruit size and fresh weight but with a higher water content compared to organic fertilization, insinuating effects on the fruit's phytochemical profile [38]. Further research is suggested on fruits of the R. canina genotypes cultivated herein in terms of the fruit's phytochemical profile to draw a more integrated picture on the cultivation protocol.…”
Section: Rosehip Development Patterns and Yield Of Cultivated Greek R...mentioning
confidence: 98%
See 2 more Smart Citations
“…From the current data, the fact that larger fruits had a similar cumulative weight to smaller fruit, may indicate variations in crop load in terms of the response of distinct genotypes to fertilization treatments; however, from the current results, no clear conclusion can be drawn. In wild germplasm of other tree crops like Amelanchier ovalis that has been experimentally cultivated, the application of conventional fertilization increased the fruit size and fresh weight but with a higher water content compared to organic fertilization, insinuating effects on the fruit's phytochemical profile [38]. Further research is suggested on fruits of the R. canina genotypes cultivated herein in terms of the fruit's phytochemical profile to draw a more integrated picture on the cultivation protocol.…”
Section: Rosehip Development Patterns and Yield Of Cultivated Greek R...mentioning
confidence: 98%
“…These genotypes were previously selected for cultivation based on a multifaceted evaluation [13,14]. The site of the cultivation setup has been previously described in [14,38]. The cultivation trial consisted of 15 individuals for each genotype planted in rows/plots of 5 plants each, where a separate fertilization regime was applied in each row (5 plants) according to a completely randomized design (Figures 1 and S1).…”
Section: Experimental Cultivation Of Four Rosa Canina Genotypes Under...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some studies [25] report that S. nigra plants that grow in higher altitudes, with longer exposure to intense sunlight, accumulate higher quantities of polyphenols in their individual organs. However, the cultivation conditions usually differed from those prevailing in the natural habitat of species, which, as well as the phytochemical profile, can affect plant growth patterns in other small tree species [34,35].…”
Section: Fruit Antioxidant Potential Of Wild-growing and Cultivated G...mentioning
confidence: 99%
“…Nevertheless, via the current approach, particular germplasm accessions with high phytochemical potential under organic fertilization could be discerned, such as genotype GR-1-BBGK-19,574. Organic and conventional fertilization treatments were applied in the long-term cultivation trial presented herein (still ongoing), presenting a diversified and sustainable cropping system as opposed to traditional, conventionally managed systems [35,[40][41][42].…”
Section: Fruit Phytochemical Profile Leaf Total Phenolic Content and ...mentioning
confidence: 99%